SISTEM PEMILIHAN SISWA BERPRESTASI DI SEKOLAH MIN 1 LABUHANBATU UTARA MENGGUNAKAN METODE NAIVE BAYES: OUTSTANDING STUDENT SELECTION SYSTEM AT MIN 1 LABUHANBATU UTARA SCHOOL USING THE NAIVE BAYES METHOD - Mey Suci Br Pardosi; Munirul Ula; Rini Meiyanti (LPPM Universitas Abdurrab, 2025)
This study aims to develop a system for selecting outstanding students at MIN 1 Labuhanbatu Utara using the Naive Bayes method as a classification technique. The data used consists of 252 student records as training data and 52 records as test data. The testing results show that the system can perform classification with 100% accuracy, where all test data were correctly predicted. This proves that the Naive Bayes method is highly effective and reliable in the process of selecting outstanding students within the school environment. Furthermore, the implementation of this system facilitates and accelerates the assessment and decision-making process without compromising the accuracy and precision of the results. Thus, this system is expected to assist the school in managing and determining outstanding students more efficiently and accurately.